Customer profiling-based optimal load shaving solution using evolutionary programming technique / Muhammad Ezzad Zaqwan Zainudin - Zainudin, Muhammad Ezzad Zaqwan (2014)
Economic growth requires high-energy consumption, which leads to supply shortage problem. The world population growth contributes in significant increase in the energy consumption every day. However, there are a lot of mitigation techniques can be applied in order to manage the energy supply and ensuring each consumers consume enough energy to satisfy their load demand. Customer's load profile or daily load curve for each customer is different from one another. Thus, pre-feasibility study on each load profile is a must to ensure an efficient load optimization process. This thesis presents optimal load clipping and shifting using Evolutionary Programming (EP) technique. The problem formulation is based on the basic load clipping and load shifting knowledge. This process is conducted using the data provide by Malaysian Energy Commission (EC). The study considers several load categories namely the industrial, commercial and domestic loads. Results obtained from the study are beneficial for the basic understanding of load clipping and load shifting knowledge for the society. Evolutionary Programming technique is used to solve the optimization model of load shaving. MATLAB software is needed to put into practice the actual operation of the optimization process to provide the recommended decision, thus, avoiding system peak hour shortage problem in the future.